Does Using Planning Policy to Restrict Fast Food Outlets Reduce Inequalities in Childhood Overweight and Obesity? - Huasheng Xiang; Viviana Albani; Louis Goffe; Nasima Akhter; Amelia Lake; Heather Brown (Institute of Labor Economics (IZA), 2022)
Half of local governments in England use planning policy to promote a healthier environment. In 2015, Gateshead Council in the North-East of England was the first local authority to ban planning permission for any new fast-food outlet. We explore if this policy is associated with changes in inequalities in childhood overweight and obesity at age 10/11 by area level deprivation. Data on childhood overweight and obesity came from the National Child Measurement Programme for 2011-2020. Data on food outlets were obtained from Food Standard Agency Food Hygiene Rating Scheme for 2012-2020. Data on area level deprivation is from the Office of National Statistics. We employed a difference-in-difference approach, to compare changes in childhood overweight and obesity rates between Gateshead and five other local authorities in the North-East of England which did not use planning policy to restrict fast-food outlets. The analysis was at the Middle Super Output Area Level (MSOA). Our results showed the prevalence of overweight and obesity in the second and third most deprived quintiles of MSOAs reduced by 4.798% and 4.106%, respectively, compared with the control groups. We did not find statistically significant changes in other deprivation quintiles when comparing the control and treatment groups. Using planning policy to limit new fast-food outlets may have played a small part in reducing health inequalities in childhood weight in Gateshead when comparing with other local authorities in the North-East of England. Planning in conjunction with other policies may be a cost-effective approach to tackling inequalities in childhood weight.
Keywords: I18; J13; I14; 330; food environment; childhood weight; England; difference in difference